Monitoring functional immune responses with a cytokine release assay: ISS flight hardware design and experimental protocol for whole blood cultures executed under microgravity conditions - Buchheim, Judith-Irina; Feuerecker, Matthias; Balsamo, Michele; Vukich, Marco; Van Walleghem, Merel; Tabury, Kevin; Quintens, Roel; Vermeesen, Randy; Baselet, Bjorn; Baatout, Sarah; Rattenbacher, Bernd; Antunes, Inês; et al. (Frontiers in Physiology, 2024)
Long-term space missions trigger a prolonged neuroendocrine stress response leading to immune system dysregulation evidenced by susceptibility to infections, viral reactivation, and skin irritations. However, due to existing technical constraints, real-time functional immune assessments are not currently available to crew inflight. The in vitro cytokine release assay (CRA) has been effectively employed to study the stimulated cytokine response of immune cells in whole blood albeit limited to pre-and post-flight sessions. A novel two-valve reaction tube (RT) has been developed to enable the execution of the CRA on the International Space Station (ISS). In a comprehensive test campaign, we assessed the suitability of three materials (silicone, C-Flex, and PVC) for the RT design in terms of biochemical compatibility, chemical stability, and final data quality analysis. Furthermore, we thoroughly examined additional quality criteria such as safety, handling, and the frozen storage of antigens within the RTs. The validation of the proposed crew procedure was conducted during a parabolic flight campaign. The selected material and procedure proved to be both feasible and secure yielding consistent and dependable data outcomes. This new hardware allows for the stimulation of blood samples on board the ISS, with subsequent analysis still conducted on the ground. The resultant data promises to offer a more accurate understanding of the stress-induced neuroendocrine modulation of immunity during space travel providing valuable insights for the scientific community. Furthermore, the versatile nature of the RT suggests its potential utility as a testing platform for various other assays or sample types.